2020
DOI: 10.15386/mpr-1644
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulatory leukocyte based indices in short-term mortality of patients with heart failure with reduced ejection fraction

Abstract: Background. Pro-inflammatory signaling is mediated by a variety of inflammatory mediators which can cause myocardial apoptosis, hypertrophia, and fibrosis, and also ultimately lead to adverse cardiac remodeling. This study aimed to assess the role of circulating leukocyte-based indices in predicting the short-term mortality in patients with heart failure with reduced ejection fraction (HFrEF). Methods. In a retrospective study, patients with HFrEF admitted to a tertiary referral center between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 38 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…[14][15][16] Additionally, SII was associated with adverse outcomes in chronic heart failure and major cardiovascular events in CAD patients who received PCI, and dNLR was associated with short-term mortality in patients with heart failure. 14,17 However, dNLR correlations with clinical outcomes in ACS patients undergoing PCI remain unclear. Therefore, this study aimed to elucidate the predictive values of SII and dNLR on the long-term prognosis of ACS patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Additionally, SII was associated with adverse outcomes in chronic heart failure and major cardiovascular events in CAD patients who received PCI, and dNLR was associated with short-term mortality in patients with heart failure. 14,17 However, dNLR correlations with clinical outcomes in ACS patients undergoing PCI remain unclear. Therefore, this study aimed to elucidate the predictive values of SII and dNLR on the long-term prognosis of ACS patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on HF patients performed by Yan et al it was shown that high NLR is associated with a higher rate of major cardiovascular events in elderly patients with HF [333]. A multicenter study conducted by Delcea et al [333] confirmed that SNL correlates with disease severity and is a prognostic marker associated with an increased risk of mortality.…”
Section: змішаний стресmentioning
confidence: 97%
“…Activation of this link leads to the secretion of cortisol, and increased levels of cortisol lead to a decrease in the relative concentration of lymphocytes. Lymphopenia, found in patients with acute or chronic heart failure, regardless of etiology correlates with the severity of the disease and is a negative prognostic marker associated with increased mortality [333].…”
Section: змішаний стресmentioning
confidence: 99%
See 2 more Smart Citations